Effect of Leverage, Assets Growth, Market Capitalization and Firm Age on Profitability of Nepalese Commercial Banks (The Harvest, 2024)
The study examines the effect of leverage, asset growth, market capitalization and firm age on the profitability of Nepalese commercial banks. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are debt to equity ratio, debt to assets ratio, long-term debt to assets ratio, short-term debt to assets ratio, assets growth rate, market capitalization and firm age. The study is based on secondary data of 11 commercial banks with 110 observations for the period from 2012/13 to 2021/22. The data were collected from publications and websites of Nepal Rastra Bank (NRB), Ministry of Finance (MoF), and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of leverage, assets growth, market capitalization and firm age on the profitability of Nepalese commercial banks. The study showed that debt to equity ratio, debt to assets ratio and short-term debt to assets ratio have positive impact on return on equity. It indicates that higher the debt equity ratio, debt to assets ratio and short-term debt to assets ratio, higher would be the return on equity. In contrast, debt to equity ratio, debt to assets ratio and short-term debt to assets ratio have negative impact on return on assets. It indicates that higher the debt equity ratio, debt to assets ratio and short-term debt to assets ratio, lower would be the return on assets. Similarly, long-term debt to assets ratio and assets growth have negative impact on return on equity and return on assets. It means that increase in long-term debt to assets ratio and assets growth leads to decrease in return on equity and return on assets. Likewise, market capitalization has a positive impact on return on assets. It means that increase in market capitalization leads to increase in return on assets. However, firm age has a positive impact on return on equity and return on assets. It means that increase in firm age leads to increase in return on equity and return on assets.